A method to reveal bulk and surface crystallinity of Polypropylene by FTIR spectroscopy - Suitable for fibers and nonwovens. (October 2018) - Lanyi, Franz J.; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W.
Abstract: The crystallinity of polymers is usually determined via Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD) or density measurements. Even though DSC is an easy and fast way to determine crystallinity, it suffers of several disadvantages in the case of fibers and nonwovens. In DSC studies, the sample preparation of fiber material may be difficult, results are not calibration free and heat is introduced in the measuring process, which might lead to transitions in instable crystal structures in the polymer. XRD is able to overcome these problems but is also time consuming and complicated in terms of sample preparation and evaluation of the measurements. Furthermore, it is not possible to determine surface crystallinity or crystallinity gradients inside the specimen with both methods. Based on approaches found in literature, a method was developed which is capable of measuring the degree of crystallinity in the bulk and at the surface of Polypropylene via Fourier transformed infrared spectroscopy. A broad set of calibration samples with a wide range of degrees of crystallinity but without a crystallinity gradient was produced by cooling samples with cooling rates from 1 to 3500 K min −1 . The degree of crystallinity was then determined from the ratio of the maximum peak height at 974 cm −1 and the maximum peak height at 998 cm −1 multiplied by 61.4%. Consecutively, the transferability of the method to the measurement of fibers and nonwovens is demonstrated and verified via procedures which are already well described in literature. This method has an excellent reproducibility, spatial resolution and is capable of determining the degree of crystallinity in less than 5 min. Furthermore, this method is easy to implement and does not require further sample preparation. Graphical abstract: Highlights: Development of a method, which is able to measure surface and bulk crystallinity of Polypropylene. Method is capable of measuring surface and bulk crystallinity of fibers in a non-destructive, location-sensitive and fast way. Surface and bulk crystallinity of fibers and nonwovens produced under different processing conditions is determined. Influence of the calendaring process on bonding points and fibers spun from the melt is shown. Influence of storage time and temperature on fiber crystallinity and post-crystallization is revealed.